Genome-wide gene expression profiling of the Angelman syndrome mouse with Ube3a mutation : from genotype to phenotype - Low, Daren Juan Hsuen (2012)
Angelman syndrome (AS) is an inheritable neurodevelopmental disorder resulting from the loss of function of the ubiquitin E3A ligase (UBE3A). Clinical features of the disorder include severe mental retardation, motor incoordination and perpetual happy disposition. Associated features of AS include hypopigmentation and seizures. Despite many targets and interacting partners of UBE3A being identified, the detailed pathogenesis of the disorder, as well as how the lack of functional UBE3A upsets cellular homeostasis, remains vague. The aim of this project is to characterize the gene expression profile of the AS mouse model by performing a genome-wide microarray screening to identify differentially expressed genes and to unravel potential genotype-phenotype correlationship mechanisms. Results: Sixty-four differentially expressed genes (7 up-regulated and 57 down-regulated) in the AS mouse cerebellum were identified, which subsequent pathway analysis showed their involvement in 3 major networks including cell signaling, nervous system development and cell death. Representative genes (Fgf7, Glra1, Mc1r, Nr4a2, Slc5a7, Epha6) from each network were selected based on their functional relevance to AS and validated for their differential expression using qRT-PCR. The validation was extended towards the protein level using Western blot for Nr4a2 and Mc1r. Both showed reduction in their respective protein level in the mutant AS mouse.